Implementation of the Labor Laws in Indonesia for Formulation of Pension Reserves - Fanny Novika; Fida Fathiyah Addini; Dedi Kusdani (International Journal of Science and Society, 2023)
This study aims to modify the calculation of severance reserves, the benefits of which are paid in accordance with Law number 6 of 2023 concerning Stipulation of a Substitute Law on Job Creation. This study seeks to modify the Projected Unit Credit calculation technique by considering Pension Constant which consists of Pension Factor, Work Term Reward Factor and Entitlement Compensation Pay Factor. In this research, the calculation of severance reserves is applied to PT A which has 24 permanent employees with an average age of employees is 29.67 years and the average work term is 5.83 years. The employee's salary during the valuation period has an average of IDR 2,776,214. This research tries to find the work mortality based on the number of working population and laid-off workers in Indonesia to be the basis for termination probability. The interest rate used in this research is the average return on bonds published by the Indonesian Bond Pricing Agency (IBPA) in five years, which is 0.063467. This research used TMI IV to define the probability of survival and death. This assumption can be used for all companies to maintain the company's financial stability by allocating reserves to pay severance pay in three possible cases, namely severance benefits upon retirement, severance benefit if employee leaves the company between valuation year and severance benefit if employee dies between the valuation year. Based on the calculation results, the reserve that needs to be stored is Rp. 1,186,723,329.18